Research of Temperature Influence on High Weather Resistance Traction Control Unit - Lin WANG; Zhenhuan YIN; Zhen ZHAO; Shuai GONG; Zherui ZHANG (机车电传动)
In order to make traction control unit (TCU) meet the requirements of high weather resistance temperature, that is, TCU should be stored in the environment of -50~70℃ for a long time and can be turned on at -40℃, the influence of temperature on the performance of TCU should be fully consider. By setting the condition of temperature screening of components on TCU board, calculating the influence of resistance value change on system parameters under limit condition, and inquiring the characteristic curve of capacitance of ceramic capacitors of different materials changing with temperature and voltage, the selection of resistors, capacitors and other components was determined; by using FloTHERM software to simulate the influence of wind speed on CPU board heat dissipation, the TCU fan type selection was determined. In order to verify the correctness of the design, the final TCU was verified according to the test method prescribed by the national standard. The test results showed that the TCU met the requirements of high weather resistance temperature.